Cold-hearted rake eaudiobook - Kleypas, Lisa (The Ravenels, 2015)
Lisa Kleypas is back with a stunning new historical romance! Readers have long waited for the return of New York Times bestselling author Lisa Kleypas to historical romance—and now she's back with her most breathtaking yet. A twist of fate . . . Devon Ravenel, London's most wickedly charming rake, has just inherited an earldom. But his powerful new rank in society comes with unwanted responsibilities . . . and more than a few surprises. His estate is saddled with debt, and the late earl's three innocent sisters are still occupying the house . . . along with Kathleen, Lady Trenear, a beautiful young widow whose sharp wit and determination are a match for Devon's own. A clash of wills . . . Kathleen knows better than to trust a ruthless scoundrel like Devon. But the fiery attraction between them is impossible to deny—and from the first moment Devon holds her in his arms, he vows to do whatever it takes to possess her. As Kathleen finds herself yielding to his skillfully erotic seduction, only one question remains: Can she keep from surrendering her heart to the most dangerous man she's ever known?